2021
DOI: 10.1016/j.abd.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the interleukins 17A, 22, and 23 and the S100 protein family in the gingival crevicular fluid of psoriatic patients with or without periodontitis

Abstract: Background Psoriasis and periodontitis are immunologically mediated chronic inflammatory diseases. Epidemiologic evidence has linked both; however, the change of markers in gingival crevicular fluid has been poorly evaluated. Objective To evaluate the levels of IL-17A, IL-22, IL-23, S100A7, S100A8, and S100A9 in gingival crevicular fluid of psoriatic and healthy subjects with and without periodontitis and their relations to psoriasis severity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Jiménez et al. found that the total concentrations of IL-17A, IL-22 and IL-23 in gingival crevicular fluid in patients with PsO and moderate or severe periodontitis were increased compared with those in PsO patients with mild periodontitis or without periodontitis ( 99 ). At present, the therapeutic drugs for PsO have been developed from TNF-α inhibitors to IL-17A inhibitors.…”
Section: Role Of Il-17a In the Relationship Between Periodontitis And...mentioning
confidence: 99%
“…Jiménez et al. found that the total concentrations of IL-17A, IL-22 and IL-23 in gingival crevicular fluid in patients with PsO and moderate or severe periodontitis were increased compared with those in PsO patients with mild periodontitis or without periodontitis ( 99 ). At present, the therapeutic drugs for PsO have been developed from TNF-α inhibitors to IL-17A inhibitors.…”
Section: Role Of Il-17a In the Relationship Between Periodontitis And...mentioning
confidence: 99%
“…All patients were examined by the same team of experts, as previously described [ 29 ]. Medical history and sociodemographic characteristics such as age, sex, and active smoking habit were recorded in predefined charts by dermatologists from the San José hospital staff.…”
Section: Methodsmentioning
confidence: 99%
“…GCF samples were collected at the deepest site per quadrant as previously described [ 29 ]. Selected sites were carefully isolated with cotton rolls and gently air-dried with an air syringe to prevent saliva contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although endodontic infections have a polymicrobial nature, black-pigmented bacteria, such as Prevotella and Porphyromonas spp., have been recognized as central agents in the development and progression of the lesion [ 8 , 9 , 10 ]. Among them, Porphyromonas endodontalis ( Pe ) and Porphyromonas gingivalis ( Pg ), stand out because of their high prevalence and virulence factors in AP [ 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%